2019
DOI: 10.3390/molecules24224194
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant System and Biomolecules Alteration in Pisum sativum under Heavy Metal Stress and Possible Alleviation by 5-Aminolevulinic Acid

Abstract: Environmental pollution is the most serious problem that affects crop productivity worldwide. Pisum sativum is a leguminous plant that is cultivated on a large scale in the Nile Delta of Egypt as a winter crop, and many of the cultivated fields irrigated with drainage water that contained many pollutants including heavy metals. The present research aimed to investigate the impact of Cd and Ni on the biochemical and physiological processes in P. sativum and evaluate the potential alleviation of their toxicity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 62 publications
5
24
0
Order By: Relevance
“…A remarkable increase in lipid peroxidation along with the higher accumulation of H 2 O 2 was observed in O. sativa seedlings grown under nickel (Ni; 0.25 and 0.5 mM NiSO 4 , 72 h) toxicity [ 98 ]. El-Amier et al [ 99 ] also reported similar results with lower levels of Ni (100 µM Ni as NiCl 2 ) in Pisum sativum . On the other hand, cadmium (Cd) stress has been shown to increase MDA, H 2 O 2 , and O 2 •– levels in different crops [ 100 , 101 , 102 ].…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 61%
“…A remarkable increase in lipid peroxidation along with the higher accumulation of H 2 O 2 was observed in O. sativa seedlings grown under nickel (Ni; 0.25 and 0.5 mM NiSO 4 , 72 h) toxicity [ 98 ]. El-Amier et al [ 99 ] also reported similar results with lower levels of Ni (100 µM Ni as NiCl 2 ) in Pisum sativum . On the other hand, cadmium (Cd) stress has been shown to increase MDA, H 2 O 2 , and O 2 •– levels in different crops [ 100 , 101 , 102 ].…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 61%
“…The Cd may bind to the carbohydrates of cell walls and the thiol groups of enzymes that exchanges metal ion concentrations such as Mg, Zn, and Fe (Iannelli et al 2002). Proline increases the tolerance of plants to heavy metals through metal chelation in the cytoplasm (Zengin and Kirbag 2007), scavenging hydroxyl radicals (Xing et al 2010), inhibit lipid peroxidation (Li et al 2013), maintaining the water balance (Mallick 2004), and the protection and stabilization of protein synthesis (El-Amier et al 2019). According to Tripathi and Gaur (2004), proline reduced the uptake of Cu by plant cells, and probably stabilized the plasma membrane, thus mitigating the toxic effects of Cu to the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Metals/metalloids toxicity interrupts not only morpho-physiological traits but also causes enhanced oxidative stress resulting from lack of balance between antioxidant defense system and ROS production [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. El-Amier et al [ 90 ] reported increased levels of LPO and H 2 O 2 accumulation in Ni (100 µM) stressed Pisum sativum L. seedlings. Such increments of oxidative stress indicators was even higher in the same crop with the same concentration of Cd as well.…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 99%